Apixaban for treatment of embolic stroke of undetermined source (ATTICUS randomized trial): Rationale and study design - Geisler, Tobias; Bäzner, Hansjörg (International journal of stroke, 2017)
RationaleOptimal secondary prevention of embolic stroke of undetermined source is not established. The current standard in these patients is acetylsalicylic acid, despite high prevalence of yet undetected paroxysmal atrial fibrillation.AimThe ATTICUS randomized trial is designed to determine whether the factor Xa inhibitor apixaban administered within 7 days after embolic stroke of undetermined source, is superior to acetylsalicylic acid for prevention of new ischemic lesions documented by brain magnetic resonance imaging within 12 months after index stroke.DesignProspective, randomized, blinded, parallel-group, open-label, German multicenter phase III trial in approximately 500 patients with embolic stroke of undetermined source. A key inclusion criterion is the presence or the planned implantation of an insertable cardiac monitor. Patients are 1:1 randomized to apixaban or acetylsalicylic acid and treated for a 12-month period. It is an event-driven trial aiming for core-lab adjudicated primary outcome events.Study outcomesThe primary outcome is the occurrence of at least one new ischemic lesion identified by axial T2-weighted FLAIR magnetic resonance imaging and/or axial DWI magnetic resonance imaging at 12 months when compared with the baseline magnetic resonance imaging. Key secondary outcomes are the combination of recurrent ischemic strokes, hemorrhagic strokes, systemic embolism; combination of MACE including recurrent stroke, myocardial infarction, and cardiovascular death and combination of major and clinically relevant non-major bleeding defined according to ISTH, and change of cognitive function and quality of life (EQ-5D, Stroke Impact Scale).DiscussionEmbolic stroke of undetermined source is caused by embolic disease and associated with a high risk of recurrent ischemic strokes and clinically silent cerebral ischemic lesions. ATTICUS will investigate the impact of atrial fibrillation detected by insertable cardiac monitor and the effects of early anticoagulation with apixaban compared with antiplatelet therapy with acetylsalicylic acid on the incidence of new ischemic lesion after embolic stroke of undetermined source.
Gesehen am 26.09.2018
First published November 23, 2016